Teaching happiness to students – implementation and evaluation of a program aiming at promoting wellbeing in elementary schools - Rahm, Tobias; Oberlehberg, Nicole; Mayer, Axel (Frontiers in Psychology, 2024)
Since the beginning of the COVID-19 pandemic, the prevalence of mental disorders in children and adolescents has increased significantly. Evidence shows that childhood mental disorders can have serious consequences on psychosocial, cognitive, and physical development. Approaches from Positive Education go further than the urgently needed prevention of mental disorders by aiming directly at promoting subjective, psychological, and social well-being. The present study describes the implementation of a brief program to promote well-being in 15 elementary schools. For this purpose, in a regular university seminar, students of teaching and educational science were instructed to give 11 ”happiness lessons“ for fourth graders in a team of two and in the presence of the class teacher over the course of three months. Quantitative data were collected from children and parents in the treatment group classes and in the parallel classes serving as the waiting control group at four measurement points (pre, post, 1- and 2-month follow-up). We assessed psychological well-being, negative emotions & moods, parent support & home life, perception of the school environment, and self-esteem of the children with established instruments with versions for children and their parents and the frequency of positive and negative emotions of the children in self-report only. Additionally, we applied ad hoc items on subjective perception of the project and open questions in the treatment group. Data were analyzed with EffectLiteR using multigroup structural equation models. Results showed a small significant effect for negative emotions with the children’s data and a medium effect for psychological well-being in the perception of the parents at the 1-month follow-up. Interaction effects suggest that lower baseline levels in parent support & home life and self-esteem would increase the treatment effect for these constructs. The need for more grounded framework in positive education and the inclusion of more qualitative methods as well as suggestions to improve the program in the sense of a whole school approach are discussed.